Immigrant parents' experiences of accessing child healthcare services in a host country: A qualitative thematic synthesis. (30th April 2020) - Karim, Nadhira; Boyle, Breidge; Lohan, Maria; Kerr, Claire
Abstract: Aim: To explore voluntary immigrant parents' experiences of child healthcare services in host countries. Design: Thomas and Harden's qualitative thematic synthesis method. Data Sources: Five electronic databases (CINAHL, Medline, PubMed, Psych INFO and Web of Science), were systematically searched from January 2000 ‐ October 2018. Review methods: Included studies focused on voluntary migrant/immigrant parents' experiences of child healthcare services. Data were abstracted independently by two authors. Critical Appraisal Skills Programme tools were applied, and qualitative thematic synthesis was performed. Findings: Nine studies were eligible for inclusion. Five descriptive themes were identified: (a) seeking information and reassurance, (b) seeking information from "people like me", (c) comparison between child healthcare services in home and host countries, (d) effective communication, and (e) cultural isolation and perceived discrimination. Three analytical themes emerged: navigation of parenting in a health context in a new environment; trust; and balance. Conclusions: Many immigrant families reported positive experiences, others felt patronized and disrespected, leading to a lack of trust and making them less willing to access universal child health care. Trusted advocates, who are culturally competent, have a role in helping immigrant parents navigate the child healthcare system and negotiate with healthcare professionals. Health registration of children of immigrants may encourage the uptake of universal healthcare services. More research is required into the specific health needs of voluntary immigrants. Impact: Less is known about the experiences of voluntary immigrants than those of refugees/asylum seekers in accessing child healthcare. Navigating health systems is difficult. This can be due to language difficulties, differences in systems of healthcare, and differences in culture/health beliefs. When both parties have some understanding of the others' healthcare practices and beliefs, balance can be found; helping the families to positively compare healthcare and incentivising them to engage in universal child healthcare. Abstract : 目的: 探讨自愿移民的父母在移民接受国经历的儿童保健服务。 设计: 托马斯和哈登的定性主题综合法。 数据来源: 对5个电子数据库在2000年1月至2018年10月期间的内容进行系统性的检索(CINAHL护理学数据库、Medline联机医学文献分析和检索系统、PubMed因特网生物医学信息检索系统、Psych INFO心理学文摘数据库和Web of Science科研数据库平台)。 审查方法: 纳入侧重自愿移居/移民父母经历的儿童保健服务的研究。由两位作者独立提取数据。应用文献严格评价项目工具和使用定性主题综合法。 发现: 9个研究项目符合纳入标准。确定了五个描述性主题:(a)寻求信息和宽慰, (b)向"同经历的人"寻求信息, (c)原籍国和移民接受国之间儿童保健服务的比较, (d)有效的沟通, 以及(e)文化疏离感和感知歧视。出现了三个分析主题:新环境下父母在儿童保健服务方面的导引;信任;平衡。 结论: 许多移民家庭在这一方面的体验向好, 但有些家庭感到屈尊降贵、不受尊重, 从而对他们缺乏信任感, 不太愿意使用常规性的儿童保健服务。而深受这些移民父母信赖的代表其利益的人员有着相应的高学识, 能够在引导移民父母使用儿童保健系统以及与医护专业人士谈判中发挥作用。对移民者的子女进行健康登记或许能推动常规性保健服务的普及。有关自愿移民者的具体健康需求方面, 需要开展更多的研究。 影响: 与难民/寻求庇护者相比, 人们对自愿移民者在使用儿童保健服务方面的体验知之甚少。引导其使用卫生体系的工作困难重重。有因为语言障碍、医疗体系的差异以及文化/健康信仰的差异等诸多原因。在两者之间对彼此的医疗实践和信仰都有一定了解的时候, 便能从中找到平衡点;帮助家庭积极比较医疗服务, 激励他们参与常规性的儿童保健服务。